Desafios e possibilidades: a luta por (re) costurar a vida - Silva, Paula Ravagnani [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This work depicts within the global to the local, the world of work before their historic, economic, social and cultural trajectory opposite the restructuring process and all “facets” arising from this process. Out of which, by means of outsourcing and the informal labor process, consolidated means of survival, especially to many women workers, who saw through the precarious work, means of survival, in the meantime, the city of Franca-SP, known worldwide for the production of the male footwear if with all the goings economic and social ills of these trends with the reality of its population. This scenario was fertile ground for the flowering of the sewing shops for lingerie in the city of Franca-SP field, considering that with these new trends, linked to culture footwear, if configured to the various forms of instability, evasion Rights, multiple functions attached by women in this context, affected and frayed family relationships, the culture of individualism that pervades the denial of collective strength and as an agent of transformation of reality given. In this dimension, we contemplate the importance of praxis Solidarity Economy that aims to empower the precarious society under the local development, with the mediation of professional committed to its Code of Ethics Social Worker, for the contribution to social transformation, giving voice to those who have, through the method of oral history, providing the perspective from local to global

O presente trabalho retrata no âmbito do global ao local, o mundo do trabalho, diante de sua trajetória histórica, econômica, social e cultural frente ao processo de reestruturação produtiva e todas as “facetas” advindas desse processo. Dentre as quais, por meio do processo de “terceirização” e do trabalho informal, consolidou alternativa de sobrevivência, principalmente, a muitas mulheres trabalhadoras, que viram por meio do trabalho precário, meio de sobrevivência, nesse ínterim, o município de Franca-SP, conhecido mundialmente pela produção do calçado masculino, se cochou com todas as “mazelas” econômicas e sociais vindas dessas tendências junto à realidade da sua população. Esse cenário foi campo fértil para o afloramento das oficinas de costura de lingerie no município de Franca-SP, haja vista, que junto a essas novas tendências, atreladas a cultura do calçado, se configuraram várias formas de precarização, sonegação de Direitos, múltiplas funções aderidas pelas mulheres nesse contexto, relações familiares afetadas e desgastadas e a cultura do individualismo que permeia a negação do coletivo como força e agente de transformação da realidade concreta dada. Nessa dimensão, contemplamos a importância da práxis da Economia Solidária que visa o “empoderamento” da sociedade precarizada no âmbito do desenvolvimento local, junto à mediação do profissional Assistente Social compromissado com seu Código de Ética, para a contribuição pela transformação social, dando “voz” a quem não tem, por meio do Método da História Oral, provendo a perspectiva do local ao global
Keywords: Serviço social com mulheres - Franca (SP); Economia solidária; Trabalho informal - Aspectos econômicos; Trabalho feminino - Aspectos sociais; Social service